An Exploration of Opportunities for Quantified-Self Technology in Diabetes Self-Care: A Systematic Literature Review - Mutunhu, Belinda; Chipangura, Baldreck; Singh, Shawren (Journal of Health Informatics in Africa, 2024)
Background and Purpose: To avoid the adoption of quantified-self technologies for diabetic self-care by trial and error, this study investigated quantified-self opportunities. The premise of the study was that the adoption of quantified-self technologies should be preceded by knowledge of the opportunities that are provided by the technology. In this respect, the research search question was, ‘What are the opportunities for the use of quantified self technology in the management of diabetes in developing countries?’.Methods: A systematic literature analysis was carried out to answer the research question. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed to select articles from four databases, which are PubMed, ProQuest, Web of Science and Science Direct. A total of 50 peer-reviewed journal and conference articles published between 2018 and 2024 were analysed.Results: Literature analysis uncovered four opportunities for using quantified-self technologies in the management of diabetes. Opportunities include monitoring, adherence, reduced cost, and data collection and sharing.Conclusions: The identified opportunities are informative and empower diabetic patients with knowledge that helps them with decision making prior to the adoption of quantified-self technologies for diabetic self-care. The results of this study are equally applicable to the adoption of any other technology, as it is important that the opportunities brought by a technology should be known before its adoption.